Perancangan UI/UX Aplikasi Panggilan Darurat Pada Command Center 112 Surabaya Menggunakan Metode Design Sprint - Thoriq Satria Marvy; Tri Sagirani; Nunuk Wahyuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Command Center 112 Surabaya is an innovation of services in disaster management supported by BPB Linmas Surabaya. Command Center 112 Surabaya service can integrate various Regional Device Organizations related to disaster management or emergencies experienced by the people of Surabaya quickly and responsively. The problem that occurs in Command Center 112 Surabaya is often receive false news reports related to emergencies numbering 704 during 2020 and the public is less responsive to report if there is an emergency to Command Center 112 Surabaya because the public has to wait a few minutes when the incoming call on number 112 is busy and the public is still hesitant when calling number 112 will be charged pulse fees. Based on the problem, Command Center 112 Surabaya needs a prototype display of android-based applications that can solve the current problem. On the emergency call application the public can report an emergency with a verified report according to the circumstances at the scene and a quick response from the operator officer to receive a report. Ui/UX design of Emergency Call application in Command Center 112 using sprint design method. There are 5 stages, namely, understand, diverge, decide, prototype, and validate. Prototype A and prototype B are designed based on the alterntif idea chosen at the decide stage. In the validate process using A/B Testing method to 10 potential users who have characteristics aged 18-40 years. The first stage of voting both prototypes by way of the user is shown a feature image of prototype A and prototype B. The results obtained by the user are more dominant choosing the look of prototype A that will be used to design prototype C. After designing prototype C, the user can try and give feedback for the improvement of prototype C. The result of the prototype C repair is that on the entrance page there are three entrances to make it easier to report and users can video call directly with the officer to request emergency handling on the emergency call application.